Near-infrared single-photon spectroscopy of a whispering gallery mode resonator using energy-resolving transition edge sensors. (28th April 2015) - Förtsch, Michael; Gerrits, Thomas; Stevens, Martin J; Strekalov, Dmitry; Schunk, Gerhard; Fürst, Josef U; Vogl, Ulrich; Sedlmeir, Florian; Schwefel, Harald G L; Leuchs, Gerd; Nam, Sae Woo; Marquardt, Christoph
Abstract: We demonstrate a method to perform spectroscopy of near-infrared single photons without the need of dispersive elements. This method is based on a photon energy resolving transition edge sensor and is applied for the characterization of widely wavelength tunable narrow-band single photons emitted from a crystalline whispering gallery mode resonator. We measure the emission wavelength of the generated signal and idler photons with an uncertainty of up to 2 nm.